Less is more: Development and evaluation of an interactive e‐atlas to support anatomy learning. Issue 2 (9th May 2014) - Guy, Richard; Pisani, Heather R.; Rich, Peter; Leahy, Cathy; Mandarano, Giovanni; Molyneux, Tom
<x xml:space="preserve">Abstract</x> An Interactive electronic Atlas (IeA) was developed to assist first‐year nursing students with interpretation of laboratory‐based prosected cadaveric material. It was designed, using pedagogically sound principles, as a student‐centered resource accessible to students from a wide range of learning backgrounds. It consisted of a highly simplified interactive interface limited to essential anatomical structures and was intended for use in a blended learning situation. The IeA's nine modules mirrored the body systems covered in a Nursing Biosciences course, with each module comprising a maximum of 10 pages using the same template: an image displaying a cadaveric specimen and, in most cases, a corresponding anatomical model with navigation panes (menus) on one side. Cursor movement over the image or clicking the menu highlighted the structure with a transparent overlay and revealed a succinct functional description. The atlas was complemented by a multiple‐choice database of nearly 1, 000 questions using IeA images. Students' perceptions of usability and utility were measured by survey (n = 115; 57% of the class) revealing mean access of 2.3 times per week during the 12‐week semester and a median time of three hours of use. Ratings for usability and utility were high, with means ranging between 4.24 and 4.54 (five‐point Likert scale; 5 = strongly agree). Written responses told a similar story for both usability and utility. The role of providing basic computer‐assisted learning support for a large first‐year class is discussed in the context of current research into student‐centered resources and blended learning in human anatomy. Anat Sci Educ 8: 126–132. © 2014 American Association of Anatomists.